2013
DOI: 10.1177/1098300713503685
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up School-Wide Positive Behavioral Interventions and Supports

Abstract: Scaling of evidence-based practices in education has received extensive discussion but little empirical evaluation. We present here a descriptive summary of the experience from seven states with a history of implementing and scaling School-Wide Positive Behavioral Interventions and Supports (SWPBIS) over the past decade. Each state has been successful in establishing at least 500 schools using SWPBIS across approximately a third or more of the schools in their state. The implementation elements proposed by Sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 38 publications
2
68
0
Order By: Relevance
“…These results provide some empirical support for the survey findings of Horner et al (2014), which showed that capacity at the state level was perceived as critical to ensuring the sustained implementation of SWPBIS. The results are also somewhat surprising, given the emphasis of previous research on school-level factors such as administrator support and staff commitment.…”
Section: Varying Importance Of Support By Levelsupporting
confidence: 78%
“…These results provide some empirical support for the survey findings of Horner et al (2014), which showed that capacity at the state level was perceived as critical to ensuring the sustained implementation of SWPBIS. The results are also somewhat surprising, given the emphasis of previous research on school-level factors such as administrator support and staff commitment.…”
Section: Varying Importance Of Support By Levelsupporting
confidence: 78%
“…Secondary interventions, or Tier 2, are typically implemented with a small group of students and include strategies such as Check and Connect (Anderson, Christenson, Sinclair, & Lehr, ), Check‐in/Check‐out (Crone, Hawken, & Horner, ), and Social Skills Groups (Lane et al, ). Lastly, tertiary intervention, or Tier 3, typically includes functional behavior assessment‐based behavioral intervention plans to target the most intensive behavioral needs of individual students (Horner, Kincaid, Sugai et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Criminology & Public Policy (Fixsen, 2009;Horner et al, 2014;Spicer et al, 2014). The denominator and the quality of the numerator both need to be defined and operationalized when determining scale and assessing social impact.…”
mentioning
confidence: 99%